THE USE OF CONTEXTUAL TEACHING & LEARNING METHOD IN WRITING DRAMA SCRIPT - Widia Tamara; Rifki; Helmiyadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research aims to improve the skill of writing drama scripts among tenth-grade students of SMA Negeri 1 Lhokseumawe through the Contextual Teaching and Learning (CTL) method. This research is a classroom action research conducted in 2 cycles. The subjects of the research are students and the Indonesian language teacher of eighth grade at SMA Negeri 1 Lhokseumawe. Data sources include: learning events, informants, and documents. Data collection techniques used are observation, interviews, tests, and document analysis. Data validity testing uses triangulation techniques for methods and data sources. Data analysis techniques use comparative descriptive and critical analysis techniques. The use of the Contextual Teaching and Learning method has been proven to improve students' skills in writing drama scripts. The results are: 1) the use of the Contextual Teaching and Learning method can improve the quality of the drama script writing learning process, and 2) the use of the Contextual Teaching and Learning method can improve students' skills in writing drama scripts. This can be seen from the increase in students' interest, learning attitudes, and the results of their drama script writing skills.